Impact of excessive smartphone usage (ESU) on online distance learning (ODL) from ergonomic perspective among public university students in Klang Valley, Selangor, Malaysia - Mohd Yusof, Irwan Syah; Abd Halim, Muhammad Shaifudin; Radzlan, Rohaizahtulamni; Badari, Shamsul Azahari; Jamaluddin, Askiah (Human Resource Management Academic Research Society, 2022)
The number of smartphone users in Malaysia continues to rise. In 2015, the nation had approximately 14.5 million smartphone users, and this figure is predicted to climb to more than 20 million by 2020. During the COVID-19 pandemic, the rate of smartphone use among public university students has risen since Online Distance Learning (ODL) was adopted, and students must adhere to it to stay safe and away from the Covid-19 virus. The aim of this study is to investigate the ergonomic effects of excessive smartphone usage among public university students in Klang Valley, Selangor, Malaysia. A cross-sectional study was conducted, with 200 public university students from Klang Valley taking part. Non-probability sampling was utilized, and data was gathered using a set of online surveys created by Google Form. The data was analyzed using SPSS software version 20.0, and Chi-square was used to examine the association of health problems with MSDs. The majority (46.0 %) are between the ages of 22 and 23, and 55.0 % are female. The Chi-square test revealed that a few factors are associated with musculoskeletal disorders and excessive smartphone usage (MSDs). Excessive smartphone usage has been shown to have a negative influence on human health, both physically and emotionally. Further studies should cover all public universities and schools in Malaysia's area to investigate the influence of excessive smartphone usage during COVID-19 during ODL, as well as other activities, to generate better data and findings.